2017
DOI: 10.7759/cureus.1776
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Vertebral Compression Fractures After Previous Vertebral Augmentation: Technical Reasons for Recurrent Fractures in a Previously Treated Vertebra

Abstract: It is well recognized that patients can develop additional vertebral compression fractures (VCF) in an adjacent vertebra or at another vertebral level after successful vertebral augmentation. Factors such as the patient's bone mineral density, post procedure activity, and chronic corticosteroid use contribute to an increased risk of re-fracture or development of new fractures in the first three months after the initial procedure. However, there is a very small subgroup of patients that have unchanged or worse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 31 publications
0
35
0
1
Order By: Relevance
“…Recompression may lead to changes in spinal balance, local kyphosis, and consequently chronic pain. Especially when there is a fracture in vertebral endplate, if the cement is not well connected with the endplate, it will provide insu cient support and lead to the continuous compression of the fracture vertebral body, which is the reason for the persistence of postoperative pain [22].He found that the long-term effect of H-type distribution of bone cement is better than O-type distribution, which is related to the closer contact between bone cement, endplates and cancellous bone in H-type distribution [23]. Our study and previous literatures show that if the bone cement is evenly distributed and closely contacted with the upper and lower endplates, it can better maintain the strength and height of the vertebral body, reduce recompression risk and eventually improve the patients' chronic back pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recompression may lead to changes in spinal balance, local kyphosis, and consequently chronic pain. Especially when there is a fracture in vertebral endplate, if the cement is not well connected with the endplate, it will provide insu cient support and lead to the continuous compression of the fracture vertebral body, which is the reason for the persistence of postoperative pain [22].He found that the long-term effect of H-type distribution of bone cement is better than O-type distribution, which is related to the closer contact between bone cement, endplates and cancellous bone in H-type distribution [23]. Our study and previous literatures show that if the bone cement is evenly distributed and closely contacted with the upper and lower endplates, it can better maintain the strength and height of the vertebral body, reduce recompression risk and eventually improve the patients' chronic back pain.…”
Section: Discussionmentioning
confidence: 99%
“…There were 26 males and 111 females, with an average age of 69 ± 7.0 years old. The average follow-up time was 15.3 ± 6.3 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months.…”
mentioning
confidence: 99%
“…The presence of previous or multiple sequential fractures is significant and changes both the immediate treatment, as well as the long-term treatment and general prognosis, including life expectancy [ 1 , 4 ]. It is important to make sure that the entire symptomatic area is included in the radiologic field and adjacent areas, such as the thoracic-lumbar junction, are adequately visualized to avoid missing junctional fractures [ 14 - 15 ]. Poor-quality plain X-ray films can occur because of technician error, patient obesity, and especially because of the poor bone detail frequently seen in osteoporotic vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…Initial films are assessed for level of fracture, percentage of collapse, and any degree of angulation or kyphosis. Scoliosis is not commonly caused by VCF but may be present secondary to underlying spinal degeneration and may complicate film interpretation and, later, any interventional procedure leading to poor pain relief or failure of vertebral augmentation [ 15 ]. A radionucleotide bone scan, showing one or more areas of positive vertebral uptake, is an important sign of fracture activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since these elderly patients frequently have lumbar stenosis (LS), often with degenerative spondylolisthesis (DS) or lumbar degenerative scoliosis (LDS), determining the cause of radiculopathy or directly relating it to the fracture can be difficult [ 6 ]. When a patient develops subsequent fractures after treatment with either vertebroplasty or kyphoplasty, it is important to differentiate between the worsening of a previously treated fracture and the development of a new fracture at an adjacent or another spinal level [ 7 ]. The reported frequency of the development of symptomatic new fractures at an adjacent level after previous vertebroplasty or kyphoplasty ranges from 10% to 29% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%